Genomic diversity of bacteriophages infecting Microbacterium spp. - Jacobs-Sera, Deborah; Abad, Lawrence A; Alvey, Richard M; Anders, Kirk R; Aull, Haley G; Bhalla, Suparna S; Blumer, Lawrence S; Bollivar, David W; Bonilla, J Alfred; Butela, Kristen A; Coomans, Roy J; Cresawn, Steven G; et al. (PloS one, 2020)
The bacteriophage population is vast, dynamic, old, and genetically diverse. The genomics of phages that infect bacterial hosts in the phylum Actinobacteria show them to not only be diverse but also pervasively mosaic, and replete with genes of unknown function. To further explore this broad group of bacteriophages, we describe here the isolation and genomic characterization of 116 phages that infect Microbacterium spp. Most of the phages are lytic, and can be grouped into twelve clusters according to their overall relatedness; seven of the phages are singletons with no close relatives. Genome sizes vary from 17.3 kbp to 97.7 kbp, and their G+C% content ranges from 51.4% to 71.4%, compared to ~67% for their Microbacterium hosts. The phages were isolated on five different Microbacterium species, but typically do not efficiently infect strains beyond the one on which they were isolated. These Microbacterium phages contain many novel features, including very large viral genes (13.5 kbp) and unusual fusions of structural proteins, including a fusion of VIP2 toxin and a MuF-like protein into a single gene. These phages and their genetic components such as integration systems, recombineering tools, and phage-mediated delivery systems, will be useful resources for advancing Microbacterium genetics.
Keywords: *Actinobacteria/vi [Virology]; *Bacteriophages/ge [Genetics]; *Genetic Variation; *Genome, Viral; Actinobacteria; Article; Bacteriophages; Bacteriophages/cl [Classification]; Bacteriophages/ip [Isolation & Purification]; Base Composition; DNA base composition; DNA, Viral; DNA, Viral/ge [Genetics]; Genes, Viral; Genetic Variation; Genome, Viral; Genomics; Microbacterium; MuF like protein; Phylogeny; VIP2 toxin; Viral Fusion Proteins; Viral Fusion Proteins/ge [Genetics]; bacterial genome; bacterial strain; bacterial toxin; bacteriophage; capsid protein; classification; comparative genomics; controlled study; dept.bio; fusion protein; gene sequence; genetic variability; genetic variation; genetics; genome size; genomics; isolation and purification; nonhuman; nucleotide sequence; peer-reviewed; phylogeny; unclassified drug; virology; virus DNA; virus fusion protein; virus gene; virus genome; virus infection; virus isolation